Water quality's responses to water energy variability of the Yangtze River - XueQi Tian; Hua Wang; Dongfang Liang; Yichuan Zeng; Yuhan Shen; Yuting Yan; Siqiong Li (Water Science and Technology, 2024)
River energy serves as an indicator of pollutant-carrying capacity (PCC), influencing regional water quality dynamics. In this study, MIKE21 hydrodynamics-water quality models were developed for two scenarios, and grid-by-grid numerical integration of energy was conducted for the Yangtze River's mainstream. Comparison of predicted and measured values at monitoring points revealed a close fit, with average relative errors ranging from 5.17 to 8.37%. The concept of PCC was introduced to assess water flow's ability to transport pollutants during its course, elucidating the relationship between river energy and water quality. A relationship model between Unit Area Energy (UAE) and PCC was fitted (R2 = 0.8184). Temporally, reservoir construction enhanced the smoothness of UAE distribution by 74.47%, attributable to peak shaving and flow regulation. While this flood–drought season energy transfer reduced PCC differences, it concurrently amplified pollutant retention by 40.95%. Spatially, energy distribution fine-tuned PCC values, showcasing binary variation with energy changes and a critical threshold. Peak PCC values for TP, NH3-N, and COD were 2.46, 2.26, and 54.09 t/(km·a), respectively. These insights support local utility regulators and decision-makers in navigating low-carrying capacity, sensitive areas, enhancing targeted water protection measures for increased effectiveness and specificity. HIGHLIGHTS Fluvial EAG spatiotemporal changes in two scenarios were explored through modeling.; Cluster exchange responses to scenario change occurred in association with reservoirs.; The budget of PCC for the Yangtze River was analyzed across multiscale dynamic processes.; The PCC values in the Yangtze River mainstream range from 0.33 to 22.98 t/(km·m).; The threshold changes the positive correlation between PCC and river energy.;